Informática e educação inclusiva: discutindo limites e possibilidades - Menezes, Eliana da Costa Pereira de (2005)
Within the themes present in worldwide discussions on education, we can currently go over the matter of the use of computer in education and the process of inclusion of students with Special Educational Needs (SENs) in regular teaching. There is constant discussion about the articulation between education and computer education for the development of an effective pedagogical practice, linked to the interests of most students and able to make feasible the overcoming of limits by the students with special educational needs Facing this reality, the following research was made, aimed at identifying how computer technology has been used by SENs' teachers in the regular teaching in Santa Maria/RS. Trying to comprehend what focus the computer can and has been used in the process of inclusion of such students, analyzing what methodologies and educational conceptions give support to the performance of the teachers before the aforementioned technology. For the data collection, there were semi-structured interviews with five teachers of four schools of regular public teaching in Santa Maria, besides a trainer teacher of the Núcleo de Tecnologia Educacional (NTE) of the city. Searching for coherence during the investigative period, but, mainly for going over an area in which the subjective aspects are purposeful, the collected data analyses were made by the quantitative approach. We conclude that despite the existing hindrances and the necessity of overcoming them in mid-term, the way in which the educational computer use is being conceived and used by teachers who have students with SENs enables the inclusion of such students. Even presenting significant limitations, the interviewed teachers' pedagogical practices are enabling all the students, with or without SENs, activities using the computer. In this way, even if the subject learning is not being directly improved, we believe that the use of computers in a democratic, equal and non-excluding way gives the students with SENs the development of autonomy, self-esteem, and social and cognitive aspects of development, which enable these students to feel part of the group, ameliorating their isolation and allowing them to interact with their classmates.